The Concept of Leadership in Islamic Perspective - Farhan Rahmawan Halim (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This paper explores the concept of leadership in Islamic perspective. Islamic leadership is based on the principles of justice, accountability, responsibility, and consultation. The paper examines the key characteristics of an Islamic leader, such as honesty, sincerity, and trustworthiness, and the importance of leading by example. It also discusses the role of a leader in promoting unity, peace, and social justice, and the need for ethical leadership in Muslim societies. The author of this paper uses the literature review method, which is a series of activities related to the method of collecting library data, reading, recording, and processing materials that are appropriate to the theme of the discussion and can be taken from library sources, either in the form of books, articles, journals, manuscripts. Publications and so on, where these sources contain theories relevant to the discussion. Based on the previous explanation, it was concluded that leaders and leadership are one unit that is important to pay attention to, especially in the sphere of Islam. Islam regulates all aspects of human life, from very big and urgent issues to even very small matters that are not even visible to human eyes, so people ignore them.